Segregated polypropylene/cross-linked poly(ethylene-co-1-octene)/multi-walled carbon nanotube nanocomposites with low percolation threshold and dominated negative temperature coefficient effect: Towards electromagnetic interference shielding and thermistors. (3rd May 2018) - Liu, Yu-Fan; Feng, La-Mei; Chen, Yi-Fu; Shi, Yu-Dong; Chen, Xu-Dong; Wang, Ming
Abstract: High-efficiently conductive networks have been well demonstrated to improve electrical properties of conductive polymer composites (CPCs). Here, a facile approach was introduced to control distribution of multi-walled carbon nanotubes (MWCNTs) in isotactic polypropylene/poly(ethylene-co-1-octene) blends (iPP/POE). The POE first melt-crosslinked by the addition of dicumyl peroxide, pulverized into small particles (40–60 meshes), then coated with iPP/MWCNTs composites, and finally compression molded to achieve the segregated iPP/POE/MWCNTs composites with MWCNTs confinedly dispersing in continuous iPP phase. This segregated structure could easily construct high-efficiently conductive networks, resulting in a low percolation threshold of 0.24 vol.%, high-performance electrical conductivity, and electromagnetic interference shielding effectiveness (EMI SE). For example, the EMI SE of ∼25 dB could be achieved in the segregated nanocomposites with 3.0 vol.% MWCNTs (thickness 1.2 mm) which reached the commercial requirement. Furthermore, the segregated samples also exhibited a relatively linear negative temperature coefficient (NTC) effect through wide temperature ranges of 45–120 °C and 150–190 °C because of anisotropic volume expansion effect caused by the segregated structure.